Weight bias in mental health settings: a scoping review - Philip, Samantha R.; Standen, Erin C.; Schueler, Jordan; Fields, Sherecce A.; Phelan, Sean M. (Frontiers in Psychiatry, 2025)
IntroductionWeight bias is a pervasive form of prejudice, most deeply and directly harming individuals in larger bodies. Although the mental health field strives to promote the delivery of equitable, culturally sensitive care, the prevalence and nature of weight bias in therapeutic contexts are not well understood. This scoping review examines how weight bias manifests within mental health settings and its impacts on client care and outcomes, exploring the issue from both client and provider lenses.MethodsA total of 43 studies meeting search criteria were identified from a systematic search process.ResultsFindings indicate that mental health professionals (MHPs) hold negative stereotypes toward larger-bodied individuals. Although MHPs were less likely to report having negative attitudes, they reported a high prevalence of weight bias in their colleagues. Studies using experimental designs demonstrated that providers’ clinical judgment and decision-making were impacted by client body size, generally showing that higher-weight clients were perceived to have lower global functioning, greater pathology, and more negative attributes than lower-weight clients. When the client was described with restrictive eating disorder symptomatology, however, MHPs rated higher-weight clients as less severe and recommended less intensive treatment compared to lower-weight clients. Qualitative studies from client samples revealed experiences of weight stigma during treatment, including MHPs’ expressions of implicit and explicit weight bias, assumptions and misattributions based on the clients’ weight, unsolicited (direct or subtle) weight loss advice, and differential treatment based on size. Experiences of weight bias were harmful to the client’s therapeutic progress and undermined their trust in their provider and the mental health system at large.DiscussionThe body of evidence suggests that weight bias is a serious and significant barrier to the provision of equitable mental health treatment and mental health equity.